Whale-watchers' perceptions of whaling in Iceland - Henderson, Erin Helen Mary, 1994- (2020)
Wild cetaceans have been an important marine resource for thousands of years, providing food for coastal communities and consumer products for whaling nations. Years of overexploitation led to a near complete ban on commercial whaling in the 1980s, after which whale-watching became the main economic use of wild cetaceans. Because whaling still takes place in several countries, there has been continued debate over whether it can coexist alongside the whale-watching industry. In Iceland, whaling and whale-watching activities both occur in the same locale, and there is concern that whale-watchers may be discouraged from visiting a country that hunts whales. Whale-watchers in Húsavík, Iceland were surveyed in July and August of 2019 to determine how the presence of the whaling industry affected their decision to go whale-watching. Questionnaires were filled out by respondents on the quay and at the Húsavík Whale Museum, located in the harbour area. A total of 224 completed questionnaires were collected and analysed to investigate demographics, booking decisions, whale meat consumption, and perceptions of whaling. Respondents were mostly young females who attended tours in Húsavík because they considered it a good whale-watching location which fit best with their travel plans. Most of those surveyed were aware that whaling took place in Iceland before booking their tour, and even prior to arriving in the country. Overall, whale-watchers were opposed to whaling, though the majority of those from a whaling nation were supportive of the practice. Additionally, while whale meat is marketed primarily to tourists, most respondents were not interested in trying it. I þúsundir ára hafa villtir hvalir verið mikilvæg auðlind fyrir sjávarbyggðir hvalveiðiþjóða, hvort sem er í formi matar og annarrar neysluvöru. Áralöng ofveiði leiddi til nær algjörs banns við hvalveiðum í atvinnuskyni á níunda áratugnum. Í kjölfar þess urðu hvalaskoðanir helsta efnahagslega nýting villtra hvalastofna. Þar sem hvalveiðar eru enn stundaðar í ...